2011
DOI: 10.1002/lary.21578
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent laryngeal nerve monitoring versus identification alone on post‐thyroidectomy true vocal fold palsy: A meta‐analysis

Abstract: This meta-analysis demonstrates no statistically significant difference in the rate of true vocal fold palsy after using intraoperative neuromonitoring versus recurrent laryngeal nerve identification alone during thyroidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
185
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(197 citation statements)
references
References 38 publications
4
185
0
8
Order By: Relevance
“…6,12,13,17,[49][50][51][52][53][54] The one published randomized control trial comparing IONM versus identification alone in bilateral thyroid surgery concluded that IONM reduced rates of transient but not permanent palsies. 55 The recent meta-analysis by Higgins et al analysed 56 There are some instances where evidence for IONM use is stronger, suggesting that it can aid in the identification of the nerve, correlating with decreased complication rates. 12,49,55,57 The large International Intraoperative Monitoring Study Group strongly advocate the use of IONM, applying its use to aid in the initial identification, dissection and prognostication of post-operative function.…”
Section: The Role Of Ionmmentioning
confidence: 99%
“…6,12,13,17,[49][50][51][52][53][54] The one published randomized control trial comparing IONM versus identification alone in bilateral thyroid surgery concluded that IONM reduced rates of transient but not permanent palsies. 55 The recent meta-analysis by Higgins et al analysed 56 There are some instances where evidence for IONM use is stronger, suggesting that it can aid in the identification of the nerve, correlating with decreased complication rates. 12,49,55,57 The large International Intraoperative Monitoring Study Group strongly advocate the use of IONM, applying its use to aid in the initial identification, dissection and prognostication of post-operative function.…”
Section: The Role Of Ionmmentioning
confidence: 99%
“…This is not the case in the dreaded bilateral RLNP [3,4]. There continues to be a debate regarding intermittent intraoperative neuromonitoring of the RLN (I-IONM), as in recent literature on the systematic use of I-IONM there was no reduction in RLNP rates [5] and the number of patients needed to be treated to avoid a RLN is relatively high [2]. A recent meta-analysis and a randomized study Paper show benefit in reducing transient RLNP in complex cases [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Probability of cost-effectiveness included observational and experimental studies (5) and another that only included randomized controlled trials (6), did not find a significant difference in RLN injury frequency when comparing neuromonitoring with the standard procedure. However, some authors still recommend the use of neuromonitoring, and the costs of implementation are unknown (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, neuromonitoring has been recommended as a novel alternative to further decrease the rate of RLN palsy (4). Two published meta-analyses did not demonstrate a statistically significant difference in the rate of RLN injury (5,6). Nonetheless, some authors suggest that its use can be cost-effective based on the decrease of sequels (7), but this argument has not been tested in the literature or the Colombian health system.…”
mentioning
confidence: 99%